In memory of Friedrich Ackermann: a personal view - Ralf W. Schroth (Geo-spatial Information Science, 2023)
PREFACEThe paper contains the author’s personal account of the professional achievements of Professor Friedrich (Fritz) Ackermann based on the author’s memories and private documents which demonstrate Ackermann’s significant influence throughout various professional phases over a period of four decades. The structure of the paper is based on the path of the author’s studies, the period as a member of the Institute of Photogrammetry at Stuttgart University, and finally, a professional career in photogrammetry, geoinformation and management. The emphasis is on the character and skills of Friedrich Ackermann. Profession, team spirit and social skills are demonstrated with impressive examples.